2007
DOI: 10.1103/physrevb.76.024505
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of the vortex slush phase in organic superconductorκ(BEDTTTF)2Cu(NCS)2

Abstract: The vortex state in a single crystal of the layered organic superconductor κ-(BEDT-TTF 2 Cu(NCS) 2 , where BEDT-TTF (or ET) is bis(ethylenedithio)tetrathiafulvalene, was studied by 1 H-NMR. Under a low field region around 0.75 T, the vortex glass-liquid transition was demonstrated by a diverging of the longitudinal nuclear spin relaxation rate and peak-broadening in spectra. Under a high field region near the upper critical field H c2 (0) ≃7 T, the curvature of nuclear spin relaxation curves showed a drastic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The NMR spectra were obtained by plotting the spin-echo amplitude against the applied field. The nuclear spin-lattice relaxation rate was obtained by tracing the spin-echo amplitude against the repetition rate of measurement [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…The NMR spectra were obtained by plotting the spin-echo amplitude against the applied field. The nuclear spin-lattice relaxation rate was obtained by tracing the spin-echo amplitude against the repetition rate of measurement [23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Recently, it has been suggested that the vortex liquid state exists even at very low temperatures resulting from quantum fluctuations instead of thermal ones, 8,9 and the resulting liquid state is a quantum vortex slush state where a short-range order of vortices remains. 9,10 In this paper, we present the flux jump as the remarkable temperature change in the sample and preceding temperature oscillation in -͑BEDT-TTF͒ 2 Cu͑NCS͒ 2 . We have measured the dependences of the flux jumps on sweep rate, field angle, and temperature to clarify the magnetothermal instability and the vortex states in this salt.…”
Section: Introductionmentioning
confidence: 99%